A Novel, Benchmark-Centered, Eco-Impact Rating System for Sunscreens and Sunscreen Formulation Design - Kunze, Gernot; Schlifke, Alexander; Jackson, Eileen; Hefner, Nicola; Berg, Katja; Vollhardt, Jürgen (Frontiers in Environmental Science, 2021)
UV filters are the key ingredients that protect human skin in sunscreens. Regardless of their chemical classification and different possible uses in broad ranges of galenic formulations, these substances are facing increasing criticism. This is due, in part, to new findings on application safety. However, there are also concerns about the occurrence of UV filters in the environment and their ecotoxicological impact and it has become difficult for personal care product companies and their formulation engineers to consider all these concerns alongside creating an efficient sunscreen product. With the ecological impact evaluation system proposed in this publication, UV filters can be selected easily without the need for specialized knowledge of environmental safety assessment. Embedded in an existing in-silico calculation system, it can be used for absorber selection during the project’s design phase without time and cost intensive investigations. In contrast to other methods, it also uses current market benchmarking to determine whether a newly developed product is indeed an improvement on the state of the art in terms of environmental compatibility. This feature can also be displayed by a logo designed for immediate understanding by consumers.